The Teaching and Learning of Reading: Its Challenges, Strategies, and Effectiveness in The Philippine Context: A Systematic Review - Casinto, Carlo Domingo (International Journal of Language and Literary Studies, 2025)
Anchored on the research objective of understanding the current challenges that confront the learning and teaching of reading skills in the Philippines’ basic education context, this systematic review study endeavors to identify the implemented intervention strategies and assess their effectiveness based on the empirical and anecdotal findings revealed in 10 published studies, coded S1 to S10, that met all the inclusion criteria for thematic analysis. The overall findings establish a clear existing need to develop multi-faceted approaches to addressing reading skill gaps, both in pedagogy and resource management. Specifically, it requires a revisit of teachers’ holistic professional training, an improvement of the readability of instructional resources, and a renegotiated collaborative partnership between schools and families.